Expected goals model with pre-shot movement, Part 1: The model - Novet, A. (2019)
There are few questions in hockey analytics more fundamental than who played well. Consequently, a large portion of hockey analysis has been focused on how to best measure results. This work is some of the most well-known work in "fancy stats"; when evaluating players and teams, many people who used to look at goals scored moved to focusing on Corsi and then expected goals (xG).